Manajemen Akhlak Muslim Dalam Surah Al Isra` Ayat 23-39 - Mulyadi Mulyadi (LPPM STAI Diniyah Pekanbaru, 2020)
Hamka said that morality is the essence of the mind that is inwardly and has been stumbled, so that it causes temperament without thinking, either noble or despicable. Thus, what is meant by moral management is how to regulate, manage, and manage matters related to morality so that good and noble character is achieved following what is ordered. The formulation of the problem in this paper is how is the moral management in Surah al-Isra` from verses 23-39 according to Hamka contained in al-Azhar's interpretation?. So the purpose of writing is to find answers to these questions using a descriptive-analytic approach. The research method in this paper is a research library or literature review